Calorific Analysis of a Granular System Made in Shape Memory Alloy - Tanapon Yachai (2020)
© Society for Experimental Mechanics, Inc. 2020. The study deals with the calorific response of a granular system made of Ni-Ti shape-memory-alloy (SMA) cylinders. SMAs belong to the family of active materials. Depending on their operating temperature, they feature unusual thermomechanical properties for metals: super-elasticity, one-way and two-way memory effects, as well as strong damping capacities. These properties take their origin from a solid-solid phase transformation accompanied by production or absorption of latent heat, which opens perspectives for the development of new heating/cooling systems. A “porous” material was built by placing SMA wires in parallel. It was subjected to confined compression with a uniaxial testing machine. Thermal measurements were performed by infrared thermography. Production and absorption of latent heat were observed in the contact zones between cylinders. Results enable us to envisage the circulation of a fluid through the SMA granular material for heat transfer.